The effect of vulcanization additives on the dielectric response of styrene-butadiene rubber compounds. (20th May 2019) - Ortega, Lucía; Cerveny, Silvina; Sill, Clemens; Isitman, Nihat Ali; Rodriguez-Garraza, Ana Lucía; Meyer, Mathias; Westermann, Stephan; Schwartz, Gustavo A.
Abstract: Rubber compounds are usually vulcanized in order to improve their mechanical properties. Although vulcanization has been largely studied in the literature, it is not completely clear how the different additives interact among them and how these affect the final properties of the compounds. Here, we present a systematic study using a combination of different experimental techniques, which allows a deeper understanding of the vulcanization mechanisms. We have studied different compounds, with and without silica filler, prepared with styrene butadiene rubber (SBR) of different microstructures and functional end groups. The dielectric response of cured and uncured samples was measured at different temperatures in a wide frequency range. In addition, we analysed the calorimetric and mechanical properties for selected compounds as well as the crosslink density. Furthermore, we performed in-situ vulcanization (in the dielectric cell) to analyse the evolution of different contributions to the dielectric spectrum during cure. Based on our results we conclude that the dielectric response of these SBR compounds is strongly affected by the presence of one of the cure accelerators used in the formulation, namely diphenyl guanidine (DPG). However, this does not affect the segmental relaxation time nor the structure of the crosslink network or the mechanical properties. This study shows the potential of broadband dielectric spectroscopy for monitoring and understanding the vulcanization mechanisms. Graphical abstract: Image 1 Highlights: Understanding vulcanization mechanisms using molecular dielectric dyes. Effect of the vulcanization additives on the dielectric response of rubber compounds. Filler-accelerator interaction in vulcanized rubber compounds. In situ monitoring of vulcanization process by means of dielectric spectroscopy.